2016
DOI: 10.1093/femsec/fiw049
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient treatments alter microbial mat colonization in two glacial meltwater streams from the McMurdo Dry Valleys, Antarctica

Abstract: Microbial mats are abundant in many alpine and polar aquatic ecosystems. With warmer temperatures, new hydrologic pathways are developing in these regions and increasing dissolved nutrient fluxes. In the McMurdo Dry Valleys, thermokarsting may release both nutrients and sediment, and has the potential to influence mats in glacial meltwater streams. To test the role of nutrient inputs on community structure, we created nutrient diffusing substrata (NDS) with agar enriched in N, P and N + P, with controls, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 68 publications
3
26
1
Order By: Relevance
“…Significance was set at a = 0.05, and all analyses were performed using R version 3.2.3 (R Core Team ). All data are available online through the Environmental Data Initiative repository (Kohler ).…”
Section: Methodsmentioning
confidence: 99%
“…Significance was set at a = 0.05, and all analyses were performed using R version 3.2.3 (R Core Team ). All data are available online through the Environmental Data Initiative repository (Kohler ).…”
Section: Methodsmentioning
confidence: 99%
“…Glacier-fed stream biofilms are generally limited by both N and P (Figure 4), but they exhibit stoichiometric flexibility and are capable of producing biomass with high C:P and N:P, which can in turn drive P limitation of consumers (e.g., macroinvertebrates, fish; Figure 4). Experimental addition of P increases microbial richness in glacier-fed streams (Kohler et al, 2016). Combined N and P additions stimulate biofilm primary production and shift microbial community composition (Robinson et al, 2003;Kohler et al, 2016 ; Figure 4).…”
Section: Trophic Interactionsmentioning
confidence: 99%
“…Experimental addition of P increases microbial richness in glacier-fed streams (Kohler et al, 2016). Combined N and P additions stimulate biofilm primary production and shift microbial community composition (Robinson et al, 2003;Kohler et al, 2016 ; Figure 4). However, hydrological characteristics (e.g., flow and proportion of glacier influence) may override the influence of nutrient additions in some areas, such as the Swiss Alps (Rinke et al, 2001) and the Tian Shan Mountains of central Asia (Ren et al, 2017b).…”
Section: Trophic Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In nutrient addition experiments, Kohler et al () found that nitrate increased Chl‐a concentrations but had little effect on AFDM in two MDV streams. In the WHC wetland, there were no strong or significant relationships between surface water nitrate concentrations and mat AFDM, Chl‐a concentration or AI (Figure S2 and Table S1).…”
Section: Resultsmentioning
confidence: 99%